Accessibility to services in rural areas. The example of petrol service provision in Germany. - Neumeier, Stefan (Routledge, 2016)
Throughout Europe, especially in rural areas, an increasing spatial concentration of basic services can be observed. As a result, the living conditions between regions are diverging. Against the background of the normative political goal of 'territorial cohesion' of the European Union, as well as the goal of German regional planning policy to provide comparable living conditions in all regions of Germany, current empirically sound information about the accessibility of basic services is important in forming an objective impression of the current situation, which can function as input for future policy interventions. Surprisingly, such data rarely exists on country level, making it difficult to realistically assess the situation. To bridge this knowledge gap we analysed the accessibility of street petrol stations in Germany, as one core service of general interest important for the overall mobility of the population especially in rural areas, based on a GIS accessibility analysis. The analysed data allows one to reason that in spite of the fact that in Germany the number of petrol stations has been steadily declining since 1970, and that Germany is one of a group of countries with the lowest density of petrol stations in Europe, provision of gasoline near to the place of residence is still, at present, guaranteed nationwide.
Keywords: Region; Regionalwirtschaft; Mobilität; Tankstelle; Standort; Erreichbarkeit; Regionalforschung; Regionale Verteilung; Ungleichheit; Versorgungsgrad